The Influence of Work Motivation and Leadership Style on Employee Performance - Eka Adila Oktapia; Caterine Darmadi; Novita Sari Raja Guk-Guk; Rafli Ramdani; Agus Agus; Agustini Tanjung (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2026)
Effective leadership and employee motivation are widely recognized as critical determinants of organizational performance; however, empirical evidence at the firm level remains essential to validate these relationships in specific contexts. This study aims to analyze the influence of leadership style and work motivation on employee performance at PT Parto Utama Medika. A quantitative approach was employed using a survey method, with primary data collected through a Likert-scale questionnaire. The data were analyzed using Structural Equation Modeling (SEM) with LISREL 8.8, including both measurement and structural model evaluations. The results reveal that leadership style has a positive and significant effect on employee performance (β = 0.57; t = 4.61), while work motivation also exerts a positive and significant influence (β = 0.40; t = 6.24). Furthermore, the model demonstrates an acceptable level of goodness-of-fit (RMSEA = 0.052; CFI = 0.94; GFI = 0.91), indicating that the proposed structural model is empirically supported. These findings suggest that strengthening communicative and participative leadership practices, alongside achievement-oriented motivational strategies, can enhance employee performance and contribute to a more productive and adaptive organizational environment.